Social capital as a determinant of business innovativeness = Kapitał społeczny jako czynnik determinujący innowacyjność przedsiębiorstw - Skawińska, Eulalia; Zalewski, Romuald I. (Zielona Góra: Faculty of Economics and Management Press)
The problem of innovativeness and competitiveness of the Polish economy is rising to strategic importance in the new EU financial perspective for 2014-2020. It is strongly related to social capital. This paper contains the results of the research on the relationship between social capital and innovative companies and the existing barriers to the implementation of innovative functions by this capital in Greater Poland. The data used have come from independent studies carried out on two collectivities of managers. Each one was composed of about 150 participants.
Keywords: kapitał społeczny; innowacyjność biznesu; bariery innowacyjności; potencjał innowacyjny pracowników; social capital; business innovation; barriers to innovation; innovation potential of employees